Metastatic Mucinous Carcinoma of the Sigmoid Colon Mimicking a Mucinous Borderline Tumor of the Ovary: A Learning Lesson - Dogra, Natasha; Singh, Abhishek; Shelly, Divya; Das, AK (Annals of Pathology and Laboratory Medicine, 2025)
Mucinous tumors of the ovary are a diverse group of neoplasms with varying degrees of malignant potential. Metastatic colorectal cancer can occasionally present in the ovary, mimicking primary ovarian mucinous tumors on morphology. This report describes a case of metastatic mucinous carcinoma of the colon masquerading as a mucinous borderline tumor of the ovary on morphology, highlighting the diagnostic challenges and the importance of a multidisciplinary approach in such cases.